Comparative efficacy of polidocanol and sodium tetradecyl sulfate in the management of oral mucoceles - A comparative study - Trupti V Gaikwad; Anuj P Maini; Sunil Mishra; Sukanya Das; Subhadeep Gupta; Malabika Shil (Wolters Kluwer Medknow Publications, 2023)
Background: Mucoceles are mucous-filled cavities. Sclerotherapy with various advantages over surgery has evolved in the dental field to treat this lesion. Objectives: To evaluate and compare the efficacy of polidocanol and sodium tetradecyl sulfate in the management of oral mucoceles. Materials and Methods: Thirty-two patients diagnosed with oral mucoceles were selected and randomly allocated into groups A and B. The 16 selected patients of group A were given sclerosant therapy with polidocanol, and the remaining 16 patients of group B were given sclerosant therapy with sodium tetradecyl sulfate at weekly intervals depending upon the regression of the lesions. The size of the lesion was measured before therapy and 1 week after first injection, second injection, third injection, and fourth injection. All the patients were recalled 6 months after completion of treatment to check for recurrence. The data analysis was done using the analysis of variance test, post hoc test, and unpaired t-test. Results: A significant size reduction was seen within group 1 and group 2 (P = 0.0000). No significant difference statistically was present when group 1 and group 2 were compared showing the effectiveness of both agents. Conclusion: Both agents are equally effective in reducing the size of oral mucoceles.